PLS-SEM ANALYSIS OF SOCIAL ENVIRONMENT'S IMPACT ON MATHEMATICS DIGITAL LITERACY - Purwanto, Arie; Rusmining, Rusmining (PATTIMURA UNIVERSITY, 2024)
The rapid development of technology makes us have to be able to adapt well. Using the internet as a medium for activities is an unavoidable part. Therefore, it is necessary to learn about the ability to use the internet in activities called digital literacy. Digital literacy is a basic skill that students must have. It is no exception in the field of mathematics as one of the absolute sciences taught at every level of education. Therefore, researchers are interested in examining digital literacy in the field of mathematics. This research in general is still very rarely done, therefore it requires an in-depth understanding of theoretical studies to see the factors that influence digital literacy skills in the field of mathematics. The lack of sample size and the relativity of adequacy in fulfilling assumptions encourage the use of PLS-SEM as an alternative in analyzing the model formed. In this study, Explanatory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) are still used to build a framework and test the structural model to be formed. In addition, the method used gives researchers the freedom to express curiosity about the problem at hand. The results obtained show that the final model can be said to be good. Mathematics digital literacy skills are influenced by several main variables that are interrelated. These variables start from the carrying capacity of schools and families. These two variables will then have an impact on the readiness of teachers and students in the community to succeed or support mathematics digital literacy skills. School readiness and family support are the main keys in succeeding or improving digital math literacy skills.